Structural Engineering in the Self-Assembly of Amphiphilic Block Copolymers with Reactive Additives Micelles, Vesicles, and Beyond - Jin, Lei (Langmuir : the ACS journal of surfaces and colloids, 2021)
Control of polymer assemblies in solution is of great importance to determine the properties and applications of these polymer nanostructures. We report a novel co-self-assembly strategy to control the self-assembly outcomes of a micelle-forming amphiphilic block copolymer (BCP) of poly(ethylene oxide) (PEO) and poly[3-(trimethoxysilyl)propyl methacrylate] (PTMSPMA), PEO114-b-PTMSPMA228. With a reactive and hydrophobic additive tetraethyl orthosilicate (TEOS), the assembly nanostructures of PEO114-b-PTMSPMA228 are tunable. The swelling of the PTMSPMA block by hydrophobic TEOS increases the hydrophobic-to-hydrophilic ratio that enables a continuous morphological evolution from spherical micelles to vesicles and eventually to large compound vesicles. TEOS that co-hydrolyzes with the PTMSPMA block can further stabilize and fix these hybrid nanostructures. With high TEOS concentrations, these polymer assemblies can be further converted through thermal annealing into unique silica nanomaterials, including nanospheres, hollow nanoparticles with dual shells, and mesoporous silica frameworks that cannot be synthesized through conventional syntheses otherwise